Earnings information conveyed by dividend initiations and omissions - Healy, Paul M.; Palepu, Krishna G. (Journal of Financial Economics, 1988)
Firms that initiate dividend payments have positive earnings changes both before and after the dividend policy change, while those omitting dividend payments have negative earnings changes. Subsequent earnings changes are positively related to the dividend announcement return, and stock price reactions at subsequent earnings announcements are smaller than usual, suggesting that these earnings changes are partially anticipated at the dividend announcement. The results indicate that investors interpret announcements of dividend initiations and omissions as managers' forecasts of future earnings changes.